Compliance with antimicrobial stewardship guidelines in surgery: an observational, multidisciplinary, cohort study - Salomé Goncalves; Neyla Mohammedi; François Antonini; Alexandre Bleibtreu; Marwan Bouras; François Depret; Pierre Fillatre; Marc Garnier; Rémy Gauzit; Djamel Mokart; Véronique Mondain; Laurent Muller; et al. (World Journal of Emergency Surgery)
Abstract Purpose Antimicrobial stewardship aims to improve clinical outcomes while reducing the unintended effects of antimicrobial use. The use of antibiotics in surgical wards, except for surgical antibiotic prophylaxis, has been poorly documented. Our goal was to assess the rate of compliance with the guidelines of antibiotic prescriptions in surgical wards. Method In a single academic center, a retrospective analysis was conducted over a two-month period to assess the rate of compliance with four criteria reflecting good practice in terms of antimicrobial stewardship: (1) decision of treatment initiation in line with the guidelines, (2) adequate spectrum of antibiotics in terms of patient characteristics; (3) duration of antibiotic treatment in compliance with the guidelines, and (4) whether re-adaptation of treatment was required. Positive responses to these four criteria indicated a 100% compliance rate. A pair of experts assessed the clinical vignettes to decide the compliance of each criterion. The secondary aims were to assess whether a 100% compliance rate was associated with positive outcomes. Results Among the 1,339 single stays in surgical wards, 232 patients (17%) received antibiotics during the study period. The rate of compliance with all four criteria was 33%. In addition, 149 (64%) patients complied with indication and spectrum, and 91 (39%) patients complied with indication, spectrum, and duration. Compliance with the antimicrobial treatment was associated with improved outcomes. Conclusion Of the patients hospitalized in the surgical wards, antimicrobial stewardship guidelines were complied with in 33% patients. Full compliance with the guidelines was associated with improved outcomes.